Strategies for managing barriers and challenges to adopting new technologies - Jackson, Denise; Allen, Christina; Michelson, Grant; Munir, Rahat (CPA Australia, 2022)
The commissioned report examines the extent to which new technologies (Customer Relationship Management, Enterprise Resource Planning, Robotic Process Automation, Blockchain, Artificial Intelligence, and Cloud Computing) are employed by businesses and accounting firms of all sizes in Australia and Southeast Asia. In doing so, it identifies the barriers and challenges to technology adoption and explores strategies for successful implementation of technology. The report reveals new insights and further advances university, industry (broadly defined), government, and professional association practices that strengthen technology adoption thereby enhancing firm competitiveness and productivity.